Meta Analysis on Direction of Accounting Standards for Islamic Financial Institution: Case Studies in United Kingdom and Indonesia - Mukhlisin, Murniati; Antonio, Muhammad Syafii (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2018)
This paper is to analyse determinants that influence implementation of accounting standards for Islamic financial institutions. It’s done by examining the history of accounting standards and two different contexts as applied to Islamic financial institutions in the United Kingdom and Indonesia. The paper adopts meta-analysis method by exploring available texts and literature with the goal to learn 'what is going on here?' and to investigate social phenomena without explicit expectations. Employing the Ibn Khaldun perspective, this study analyses two determinants i.e. institutional setting that may be suitable in the context of the United Kingdom, and accounting needs in the case of Indonesia. The research shows the determinants are well fitted with interdisciplinary characters of Ibn Khaldun model of civilization.DOI: 10.15408/aiq.v10i1.5676